Resubmission of VO#14 - Adjustment unit price for R.C.C works in foundation with water proofing admixture - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding resubmission of VO#14 - Adjustment unit price for R.C.C works in foundation with water proofing admixture of BRAC University new campus project.